Embryotoxicity assays for leached components from dental restorative materials - Mummolo Stefano; Tecco Simona; Gallusi Gianni; Farini Donatella; Klinger Francesca G; Marzo Giuseppe; Libonati Antonio; De Felici Massimo; Campanella Vincenzo (BMC, 2011)
Abstract Background Currently, there are no suitable assays available to evaluate the embryotoxicity of leached components from restorative dental materials. Methods The effect of the medium conditioned by composites and amalgam on mouse blastocysts in vitro was tested. The materials were also subcutaneously implanted, and the effect of the medium supplemented with serum from the host blood was evaluated in the embryotoxicity assay. The embryo implantation rate in the material-transplanted mothers was also evaluated. Results The results show that while the culture in media conditioned by amalgams did not affect blastocyst development, the medium conditioned by composites caused blastocyst degeneration and apoptosis. The development of blastocysts in a medium containing serum obtained from animals after transplantation was, however, without effect. Finally, inconsistent reduction in the implantation rate in transplanted mothers was observed. Conclusions In this study, we provide examples of in vitro and in vivo tests that may be used to evaluate embryotoxicity for dental materials. Our results show that leached components from our composite-material induced embryotoxicity in vitro, however, no toxicity was observed when subcutaneously implanted in vivo. This highlights the necessity of integrated in vitro and in vivo tests for valuable predictive estimation of embryotoxicity for complex materials.